Penerapan Model Pembelajaran Kooperatif TGT Berbantuan Media Wayground Untuk Meningkatkan Hasil Belajar Peserta Didik Pada Materi Struktur Bumi Dan Perkembangannya - Pamellajoan Presidena; Ahmad Qosyim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of the learning process, student responses, and cognitive learning outcomes of students by implementing the TGT type cooperative model assisted by wayground media on the material of earth structure and its development to improve student learning outcomes. This type of research is Pre-Experimental Design) with the research design is One Group Pretest-Posttest Design. The research sample consisted of 28 students of class VIII-A SMPN 1 Baron in the 2025/2026 academic year. The implementation of learning obtained a very good category. The student response questionnaire obtained a very good category with an average overall percentage of 89%. Student learning outcomes have increased. This can be seen from the N-Gain results. The N-Gain test results obtained a value of 0.64 which means there is an increase in the moderate category. The acquisition of sig. The pretest was 0.060 and the posttest sig. was 0.085, the data were normally distributed. The t-test results showed a significant difference between cognitive learning outcomes before and after the implementation of the TGT type cooperative learning model assisted by wayground media. Based on these results, it can be concluded that the implementation of the TGT type cooperative learning model assisted by wayground media on the material of earth structure and its development can improve the learning outcomes of junior high school students.